New code for spectral-amplitude coding optical code-division multiple-access systems - Thanaa Hussein, Abd.; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Hilal Adnan, Fadhil, Dr.; R. Badlishah, Ahmad, Prof. Madya Dr.; Mohd Abdur, Rashid, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/